O-014 Cerecyte coil trial: the angiographic outcome of endovascular coiling in patients with ruptured and unruptured intracranial aneurysms treated with cerecyte coils compared with bare platinum coils. Results of a prospective randomized trial. (16th November 2010) - Molyneux, A; Fox, A; Sneade, M; Mehta, Z
Abstract : Purpose: To report the 6 month angiographic results in patients treated with Cerecyte or bare platinum coils in a prospective randomized trial. Materials and methods: 500 patients undergoing coil treatment of a ruptured or unruptured cerebral aneurysm in 23 centers in Europe, North America and Japan were randomly assigned to receive either Cerecyte Coils or bare platinum coils. The primary objective was to determine if Cerecyte coils improved the angiographic outcome on follow-up digital angiography 6 months after treatment. Angiographic follow-up was also obtained at 12–24 months after enrollment. Imaging data were transferred to a core laboratory on CD and uploaded into a PACS system and analyzed blind by an experienced neuroradiologist. Secondary objectives included whether Cerecyte coils reduced major recurrence or the need for aneurysm retreatment. Angiographic assessment was carried out by an independent core laboratory blind to the treatment allocation. Success was defined in the protocol as 'complete angiographic occlusion, improvement or no change in the angiographic appearances from the postprocedural angiography'. Results: The proportion of patients with success on the primary outcome, minor and major recurrence and retreatment rates will be reported at the first follow-up and the frequency of late recurrence of the second follow-up will be reported for all patients with available data. Conclusion: The study will provide objective evidence whether Cerecyte coils improve angiographic outcome after coil treatment of cerebral aneurysms.